Growth of Fast- and Slow-Growing Rhizobia on Ethanol - Sadowsky, Michael J. (1986)
Free-living soybean rhizobia and Bradyrhizobium spp. (lupine) have the ability to catabolize ethanol. Of the 30 strains of rhizobia examined, only the fast- and slow-growing soybean rhizobia and the slow-growing Bradyrhizobium sp. (lupine) were capable of using ethanol as a sole source of carbon and energy for growth. Two strains from each of the other Rhizobium species examined (R. meliloti, R. loti, and R. leguminosarum biovars phaseoli, trifolii, and viceae) failed to grow on ethanol. One Rhizobium fredii (fast-growing) strain, USDA 191, and one (slow-growing) Bradyrhizobium japonicum strain, USDA 110, grew in ethanol up to concentrations of 3.0 and 1.0%, respectively. While three of the R. fredii strains examined (USDA 192, USDA 194, and USDA 205) utilized 0.2% acetate, only USDA 192 utilized 0.1% n-propanol. None of the three strains utilized 0.1% methanol, formate, or n-butanol as the sole carbon source.